Identification of biomarkers and potential drug targets in DFU based on fundamental experiments and multi-omics joint analysis - Xin, Xudong; Zhou, Haidong; Huang, Song; Zhang, Wenzhao; Xu, Jiahou; Wang, Wei; Wei, Jihua; Li, Liqing (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to investigate the molecular mechanisms by which quercetin facilitates the treatment of diabetic foot ulcers (DFU).MethodsTranscriptome sequencing datasets for DFU, specifically GSE80178, GSE134431, and GSE147890, along with single-cell dataset GSE165816, were retrieved from the Gene Expression Omnibus (GEO) online database (https://www.ncbi.nlm.nih.gov/geo/). The single-cell data were subjected to processing, annotation, differential gene expression analysis, and staining. The transcriptome sequencing data were analyzed using weighted gene co-expression network analysis (WGCNA), followed by assessment of immune infiltration. By integrating transcriptomic data and differentially expressed genes identified through WGCNA, co-expressed differentially expressed genes were obtained, and a protein-protein interaction (PPI) network was constructed followed by enrichment analysis. Core genes were screened using four machine learning models (Random Forest, Lasso, XGBoost, and SVM). Drug prediction was performed to identify potential therapeutic agents, and molecular docking simulations were conducted to assess the binding interactions between the macromolecular proteins encoded by the core genes and quercetin. A rat model of diabetic foot ulcer (DFU) was established and randomly divided into three groups: control, model, and treatment groups. Tissue samples were collected at 3, 7, and 14 days post-intervention for RT-qPCR, hematoxylin and eosin (H&E) staining, Masson’s trichrome staining, and immunofluorescence staining to evaluate the therapeutic effects of quercetin via modulation of the core genes on DFU.ResultsThe analysis identified 275 differentially co-expressed genes that are extensively involved in the IL-17 signaling pathway, metabolic pathways, the PI3K/Akt signaling pathway, Staphylococcus aureus infection, complement and coagulation cascades, among others. From these, four core genes (CIB2, SAMHD1, DPYSL2, IFI44) were selected using machine learning techniques. Immune infiltration analysis demonstrated a strong correlation between SAMHD1, IFI44, DPYSL2, and macrophages. Molecular docking studies revealed that quercetin exhibits a lower binding energy with the target protein binding site, forming a stable structure. Single-cell analysis indicated that SAMHD1 is predominantly expressed in macrophages, whereas DPYSL2 is expressed not only in macrophages but also significantly in vascular endothelial cells and other cell types. This suggests that SAMHD1 and DPYSL2 may exert their effects by modulating these cells, as corroborated by basic experimental findings. The improvement in wound tissue morphology observed in the treatment group was more favorable compared to the model group. In comparison to the acute group, the gene expression profile in the model group aligned with bioinformatics predictions. Furthermore, the alterations in core gene expression following quercetin treatment were statistically significant.ConclusionQuercetin may enhance the healing of diabetic foot ulcers by modulating macrophage activity through the regulation of SAMHD1 and DPYSL2, thereby contributing to the recovery process.